HUBUNGAN ANTARA KOMUNIKASI ORANG TUA-ANAK DAN KOMUNIKASI TEMAN SEBAYA DENGAN AKTIVITAS BELAJAR SISWA KELAS 6 SD DI KECAMATAN GERIH KABUPATEN NGAWI - Siswanta, Fatihatul Mahmudah, Bedjo Sukarno & (Transformasi, 2016)
This event will be based on research by the phenomenon of lack of child learningactivities in communication the communication of parents and peers in district Gerih Ngawi.Research results obtained correlation coefficients Kendal Tau variables between Parent-childCommunication (X1) learning activities with variable grade 6 ELEMENTARY SCHOOLStudents in district Gerih, Ngawi (Y) of 0.411 Î± assignment with 5% and turns the count value isgreater than the table 0.025.33 Ï„ = 0255 which means there is a positive and significantrelationship between both variables. While the results of the test statistic relationship betweenPeer Communication (X2) with learning activities of ELEMENTARY SCHOOL Students inDistrict 6 Gerih klas Ngawi (Y) obtained the value of the coefficient of correlation of Kendal Tauof 0.350 Î±, with 5% where the value of the count turns out to be bigger than the table 0.025.33 Ï„= 0255 which means there is a positive and significant relationship between both variables.Based on the findings of the research results it can be concluded that the higher the parents 'communication with the higher students learning activity.Keywords: parent-child communication, communication peers, learning activities